KELAS MEMASAK IBU BALITA MENU DAUN KELOR UNTUK MENGATASI ANEMI DAN STUNTING - Hariyani, Tintin (Prosiding SPIKesNas : Seminar Publikasi Ilmiah Kesehatan Nasional, 2024)
Moringa (Moringa oleifera) is a multipurpose plant. Moringa can grow in lowlands and highlands up to 1,000 meters above sea level (m pl). The distribution of moringa spreads from Java, Sumatra, Kalimantan, Sulawesi, East Nusa Tenggara, and West Nusa Tenggara. The fairly high iron content in moringa leaves makes it believed to help prevent anemia. It can help relieve infections caused by bacteria. It can help increase antioxidant levels in women who have gone through menopause. Good for children who are malnourished and stunted. This community service activity was carried out by holding a cooking class. Participants in this activity were 27 people consisting of 15 pregnant women and 12 mothers of toddlers. Activities include socialization, education, demonstrations, demonstrations, and distribution of moringa plant seeds. The activity was carried out on May 30, 2023. The location of the activity was at the Minggiran village hall, Papar district, Kediri district. The menu of dishes demonstrated were moringa vegetables, moringa jelly milk, and pudding. Based on the socialization carried out, it is known that moringa leaves are plants that are known in the Kediri area. Many moringa plants grow wild or are planted in the yard area of ​​the house. A total of 12 pregnant women and mothers of toddlers have moringa plants in their homes. However, they do not yet know that the nutritional content of moringa leaves is useful for preventing and treating stunting and anemia. They only know that moringa leaves are consumed in the form of vegetables. They have never tried to process moringa leaves in different ways to produce a variety of more varied food. Variations in the moringa leaf are needed so that toddlers and pregnant women have more appetite for consuming the moringa leaf. In this cooking class activity for mothers of toddlers and pregnant women, innovation and creativity in processing moringa leaves into various menus for food, drinks, and snacks are demonstrated. will make it easier for pregnant women and children to accept and consume moringa leaves. So that mothers can cook various moringa leaf menus that are beneficial for babies and pregnant women